Newly Developed Restorer Lines of Sorghum [Sorghum bicolor (L.) Moench] Resistant to Greenbug - Evgeny E. Radchenko; Irina N. Anisimova; Maria K. Ryazanova; Ilya A. Kibkalo; Natalia V. Alpatieva (Plants, 2024)
Eight lines of grain sorghum [Sorghum bicolor (L.) Moench], which can be used as a promising source material in heterotic hybrid breeding as pollen fertility restorers and donors of resistance to the greenbug (Schizaphis graminum Rondani), are characterized. The new restorer lines (R-lines) were developed by crossing the maternal sterile line Nizkorosloe 81s (CMS A1) with two lines selected from the grain sorghum collection accessions VIR-928 and VIR-929 as the paternal forms. The R-lines were genotyped using PCR markers, and also characterized by height, duration of the seedling–flowering period, and some of the technological properties of flour. With the use of microsatellite markers linked to the Rf genes and by hybridological analysis, it was shown that the new lines carry the dominant allele of the gene Rf2. The PCoA analysis demonstrated clear differences of each R-line from the parents. The genotypes of the new lines and their parental forms for the Rf2 locus were confirmed by applying three allele-specific codominant CAPS markers which detected SNPs in the candidate Rf2 gene. All new lines were highly fertile, as demonstrated by cytological analysis of acetocarmine-stained pollen preparations. A high resistance to the greenbug was demonstrated for each new R-line both in the laboratory and field conditions against a severe aphid infestation. Grain quality parameters such as protein content and dough rheological properties varied widely and were quite satisfactory in some R-lines. Characteristics common to all eight sorghum lines studied, such as the ability to restore pollen fertility in the F1 generation, good pollen quality, greenbug resistance, early ripening, spreading panicle, and low stature, allow us to recommend them for producing commercial F1 hybrids with satisfactory grain quality for both fodder and food purposes.